Comparison of Paresthesia Mapping to Anatomical Placement in Burst Spinal Cord Stimulation: Initial Trial Results of the Prospective, Multicenter, Randomized, Double‐Blinded, Crossover, CRISP Study. Issue 5 (12th March 2020) - Al‐Kaisy, Adnan; Baranidharan, Ganesan; Palmisani, Stefano; Pang, David; Will, Onita; Wesley, Samuel; Crowther, Tracey; Ward, Karl; Castino, Paul; Raza, Adil; Agnesi, Filippo
Abstract : Introduction: In this prospective, multicenter, double‐blinded, randomized, crossover study, we compared the therapeutic efficacy of burst SCS delivered using a lead implanted with the paresthesia mapping approach to a lead implanted with an anatomic placement approach. Materials and Methods: Subjects with chronic low back pain were implanted with two leads, one using paresthesia‐mapping approach (PM) and the second using anatomical placement procedure (AP). Stimulation contacts were chosen using the standard intraoperative paresthesia‐testing procedure for the paresthesia‐mapped lead or an activated bipole overlapping the T9‐T10 junction for the anatomical lead. Amplitude for either lead was selected such that no sensory percepts were generated. Subjects were assessed at baseline and after a trial period during which they tested each lead for two weeks in random order. Eligible subjects had the option to receive permanent implants using their preferred AP or PM approach at end‐of‐trial. Results: Of the 53 subjects who completed both trial periods, 43 (81.1%) experienced at least 50% back pain relief with at least one lead. Nearly half of these (20; 46.5%) were profound responders who experienced at least 80% back pain relief with either leads. Primary and secondary outcomes, at the end of trial, showed significant improvements for both AP and PM leads from baseline yet were not significantly different from each other. Discussion: The trial results of this study suggest that similar clinical outcomes can be achieved in burst SCS when performing lead placement either using paresthesia mapping or anatomical placement with imaging references.